Bibliographie annotée concernant la pénétration de la géographie dans le Québec - Hamelin, Louis-Edmond (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1960)
As a first step towards a historical study of Geography in the Province of Québec, the author bas first gathered an abundant bibliography, the first part of which concerns the geography textbooks which have been used in Québec.Since 1804, there have been more than 300 editions or reprints of Canadian books which have been used as geography textbooks. The history of these textbooks may be divided in three periods : 1. 1804-1830, the first textbooks ; 2. 1830-1900, when the main textbooks were those by Holmes, la Société d'Education, les Frères des Écoles chrétiennes, F.-X. Toussaint and Hodgins-Lovell ; 3. the xx th century, which bas known two main collections, one by the Marist Brothers and one by uni-versity geographers. The characteristics of these textbooks are presented and the author concludes by giving a list of the textbooks that remain to be written to meet the present needs.